Identity formation in Proverbs 22 and the Mkpuru Mmiri drug crisis in Igbo communities - Uroko, Favour C. (HTS teologiese studies, 2022)
Although progress, no matter how small, has been made by scholars who examined different aspects of the Mkpuru Mmiri [methamphetamine or crystal meth] drug crisis in Nigerian Igbo communities, literature is yet to approach the study from the perspective of Proverbs 22 of the Old Testament. In this study, literature was extended to examining the Mkpuru Mmiri crisis from the lens of Proverbs 22. Today, many youths in Igbo communities are addicted to Mkpuru Mmiri, a stimulant drug. As part of the findings, it was discovered that the effects of Mkpuru Mmiri include paranoia, hallucinations, delinquency and other behaviours inimical to social well-being and even death. Addiction to Mkpuru Mmiri is seen in the increasing number of unstable young people on the streets of the various states in Igbo communities. The author of the book of Proverbs teaches how youths are to live responsible and happy lives. According to Proverbs, evil conduct will always result in divine vengeance and punishment during a person’s earthly life. The themes include ‘home and personal training (vv. 1–6)’, ‘consequences of one’s actions (vv. 4–23)’ and the ‘reasons to avoid bad company (vv. 24–29)’.Contribution: Addiction to Mkpuru Mmiri has no recognised cure. This may be seen in the growing number of unruly young people on the streets of Nigeria’s south-east states. Practical theology is one of the disciplines implicated.